Managing Product Variety to Increase Sales in Used Automotive Closed-Loop Supply Chains - Saunders, Lance W; Merrick, Jason R W; Autry, Chad W; Galbreth, Michael R; Bradley, Randy V (Production and Operations Management, 2024)
The relationship between product variety and sales has been extensively researched, but almost exclusively from the perspective of a new goods retail firm. Closed-loop supply chains for used goods, such as automobiles, offer unique challenges in terms of using reverse flows to create product variety at the retail location. Firms in used goods industries are unable to define their product mix a priori and may not even know which goods will be available to add to their sellable inventory. In this article, we use data from a used automobile retailer to explore these issues. A better understanding of the relationship between variety and sales can help used automobile retailers improve how they define and structure product variety at retail locations. Improved management of used automobile sales has obvious financial implications, but it also has important environmental implications, given the large contribution of passenger vehicles to overall emissions. This study implements a cluster analysis using consumer-facing variables to understand how customers view product variety for used automobiles. Our results show that three distinct classes of inventory exist, primarily driven by a key characteristic—body type—which differs from the traditional definition of product variety for new vehicles in the existing literature. A two-way fixed effects regression is then used to understand the relationship between product variety at the firm's retail locations and sales. The results demonstrate a nonlinear relationship between product variety and sales and, intriguingly, suggest that increasing product variety in some classes can be used to drive sales in others. Our findings yield important contributions for managers in used automobile firms and extend the broader literature on closed-loop supply chains. Specifically, our research demonstrates important differences in how product variety should be managed with used goods relative to new goods by a firm seeking to maximize sales.